Chinese college students' gender self-esteem and trans prejudice. Issue 1 (2nd January 2017) - Chen, Bing; Anderson, Veanne N.
ABSTRACT: Most studies of trans prejudice, or prejudice against transgender people, have been conducted in Western countries. The current study explored trans prejudice in a sample of 124 heterosexual college students from the People's Republic of China. We also examined the relationship between gender self-esteem—the importance of gender to one's self-identity—and trans prejudice. Results indicated that men reported more trans prejudice than women. Both women and men reported more violence toward, teasing of, and discomfort with trans women compared with trans men. Gender self-esteem was not a significant predictor of trans prejudice for men or women. These results suggest that some of the predictors of trans prejudice in Chinese people may be similar to predictors found in Western samples. However, differences may be due to cultural factors such as membership in a collectivistic versus an individualistic society.